2019
DOI: 10.1007/s11104-019-04258-9
|View full text |Cite
|
Sign up to set email alerts
|

Salinity-induced changes in the rhizosphere microbiome improve salt tolerance of Hibiscus hamabo

Abstract: Aims We aimed to assess whether soil salinity changes the microbial community in the rhizosphere of Hibiscus hamabo, and whether these changes in the microbiome feedback on the growth of H. hamabo. Methods To test effects of salinity on the rhizosphere microbiome, we first did a greenhouse experiment in which H. hamabo was grown in pots with a sand-soil mixture at different salt concentrations (0, 15, 40 and 90 mM NaCl). Then in another two experiments, we tested effects of the rhizosphere microbiomes on perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 49 publications
0
18
0
Order By: Relevance
“…As a shelterbelt tree species along the coasts, H. hamabo is a good candidate for studying responses and regulatory mechanisms under stress, which are crucial for using this species in the ecological greening of coastal vegetation systems. Some attempts have been made to understand the mechanisms of stress adaptation in H. hamabo , but the absence of genomic data has hindered systematic investigations to date [ 2 , 15 ]. Here, we report the assembly of the H. hamabo genome at the chromosome level using a combination of PacBio, Hi-C, and Illumina sequencing technology.…”
Section: Introductionmentioning
confidence: 99%
“…As a shelterbelt tree species along the coasts, H. hamabo is a good candidate for studying responses and regulatory mechanisms under stress, which are crucial for using this species in the ecological greening of coastal vegetation systems. Some attempts have been made to understand the mechanisms of stress adaptation in H. hamabo , but the absence of genomic data has hindered systematic investigations to date [ 2 , 15 ]. Here, we report the assembly of the H. hamabo genome at the chromosome level using a combination of PacBio, Hi-C, and Illumina sequencing technology.…”
Section: Introductionmentioning
confidence: 99%
“…The sole plant species that did not show any evidence of mycorrhizal fungal colonization from our survey was Hibiscus arnottianus . However, this absence could be an artifact of low replication ( n = 1) because previous studies have found evidence of AM fungal colonization in other species of Hibiscus (Koske and Gemma, 1995; Fallahi et al, 2016; Davison et al, 2018; Yuan et al, 2019).…”
Section: Discussionmentioning
confidence: 93%
“…“M6” that confers resistance to fungal pathogen Fusarium graminearum in Finger Millet 4 ), confer fitness advantages to plant host (e.g. Association of microbiome phenotypes with Arabidopsis genes involved in immunity, cell-wall integrity, root and root hair development 5 ) and increase plant tolerance to stress and drought 6 8 . In fact, plant Microbiome was identified as a key for the next green revolution 9 , and numerous products and microbiome management strategies were developed in agriculture including (i) microbiome transplants, (ii) microbial inoculants, (iii) microbial and plant extracts, (iv) methods to change environmental conditions and (V) microbiome engineering 10 12 …”
Section: Introductionmentioning
confidence: 99%